Synthesis of Ti02 N anosized Powder Photocatalyst Via Solgel Method for Bacteria Inactivation Application - Diana, Farah; Iis, Sopyan; Mel, Maizirwan (Universiti Putra Malaysia, 2011)
Titanium dioxide (Ti02) is the most widely used photocatalyst and has been applied for water and air purification and disinfection of microorganism. Anatase structured Ti02 is a wide bandgap (3.2 eV) semiconductor which, under UV light, is able to degrade chemicals and cell components of microorganisms. In this study, Ti02 nanopowder photocatalyst was synthesized by sol-gel process using a titanium chelate compound, titanium (di-isopropoxide) bis(acetylacetonate) (PTP) as the precursor. The precursor was hydrolyzed under an acidic catalyst condition, followed by reflux for 15 minutes and 1 hour. The precipitate powder obtained after filtration was calcined at 400°C. XRD analysis confirmed that the Ti02 powders A (15 minutes reflux) and B (1 hour reflux) have strongest peak at 25° which indicates anatase crystal structure. The particle size of powder A was smaller than the powder B as proved by calculation using Scherrer's equation. The crystallization temperature of Ti02 powder A was higher due to its smaller particles that needed more heat to crystallize than powder B as confirmed by TGIDTA. FESEM analysis showed powder A have homogenous spherical shape, contrast to powder B showing inhomogenous spherical shape and connected particle. The Ti02 photocatalyst activity in killing bacteria was investigated for 5 hours by varying the concentration 'of Ti02 and UV light intensity.